Marx et Sraffa - Dostaler, Gilles (L'Actualité économique, 1982)
AbstractIt has been claimed, on the one hand, that Sraffa has successfully resolved some of the theoretical problems that Ricardo had tackled without success and, on the other hand, that Sraffa offered valid solutions to another set of theoretical problems that Marx incorrectly thought he had solved, in particular the famous "transformation problem". What is exactly the basis for such claims, especially the latter?